Uji Antagonistik Paenibacillus polymyxa Jav78 terhadap jamur Colletotrichum spp. secara in vitro - Phabiola, Trisna Agung; Khalimi, Khamdan (Nandur; Vol 3 No 3 (2023), 2023)
Anthracnose disease in chili plants can cause yield loss. The purpose of this study was to determine the ability of  Paenibacillus polymyxa  Jav78 to inhibit the growth of Colletotrichum spp. and identify the antifungal compound produced by  P. polymyxa  Jav78. Antagonistic test of  P. polymyxa  Jav78 against Colletotrichum fungus was carried out in vitro. Identification of antifungal compounds using Gas Chromatography Mass Spectrometry (GCMS). The results showed that  P. polymyxa  Jav78 was able to inhibit the growth of the fungus Colletotrichum spp. with the percentage of inhibition ranging from 77.33% to 85.07%. The  P. polymyxa  Jav78 filtrate contains antifungal compounds 76.01% hexadecanoic acid, methyl ester and 16.48% imidazole-3-oxide. The results of this study provide information that  P. polymyxa  Jav78 can be used as a biofungicide to control anthracnose disease in chili plants.